Interaction of Polyphenols as Antioxidant and Anti-Inflammatory Compounds in Brain-Liver-Gut Axis - Amritpal Singh; Yu Fung Yau; Kin Sum Leung; Hani El-Nezami; Jetty Chung-Yung Lee (MDPI AG, 2020)
Oxidative stress plays an important role in the onset as well as the progression of inflammation. Without proper intervention, acute inflammation could progress to chronic inflammation, resulting in the development of inflammatory diseases. Antioxidants, such as polyphenols, have been known to possess anti-oxidative properties which promote redox homeostasis. This has encouraged research on polyphenols as potential therapeutics for inflammation through anti-oxidative and anti-inflammatory pathways. In this review, the ability of polyphenols to modulate the activation of major pathways of inflammation and oxidative stress, and their potential to regulate the activity of immune cells are examined. In addition, in this review, special emphasis has been placed on the effects of polyphenols on inflammation in the brain-liver-gut axis. The data derived from in vitro cell studies, animal models and human intervention studies are discussed.